Characterization And Wettability Of Superhydrophobic Filled Plasticized Polyvinyl Chloride - Marahat, Muhammad Hanif (Universiti Sains Malaysia, 2017)
Nowadays, superhydrophobic surfaces have become an interest in research industry. This is because the superhydrophobic surface able to be used in various applications such as coating, textile and biomedical field. The term superhydrophobic is describing the poor wettability of a surface with the contact angle greater than 150o. The objective for this research is to prepare superhydrophobic plasticized PVC filled with precipitated calcium carbonate (PCC) that was coated with stearic acid. The used of the coated filler is to lower down the surface energy of the filler particles. The effect of filler addition on plasticized PVC compounds was analyzed by tensile strength. Furthermore, the wettability and surface morphology were evaluated using field emission scanning electrode microscopy (FESEM), contact angle measurement and atomic force microscopy (AFM). Other than that, to further improved the surface roughness, technique of rubbing sandpaper with 500 grit on the coating sample was being used. It can be inferred that the addition of filler and solvent reduces the strength and flexibility of plasticized PVC compounds. The increase in filler loading will increase the modulus and toughness, while solvent introduced an opposite effect to the compound. The addition of filler was able to increase the contact angle of the plasticized PVC from 89.39o up to 126.67o. The increase in fillers along with the effect of sandpaper rubbing also increases the surface roughness which is one of the critical factors in enhancing the hydrophobicity of the compounds. However, the contact angle obtained are still not reaching the target of superhydrophobic with contact angle,θ greater than150o.